Difficulties faced by first year students of Tour guides at Thanh Hoa College of Culture & Arts in English oral presentations. - Hoang, Thi Hue (ĐHNN, 2017)
The importance of English oral presentation is undeniable in the Tour guiding work. Therefore, understanding the students of Tour guides’ difficulties in learning English oral presentation skill is apparently necessary to gain effective ESP teaching and le (...)